Environment-friendly, low-cost, recyclable large-scale synthesis of zif-67 material and method thereof
Patent Information
- Application Number
- CN202411373745.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-09-29
AI Technical Summary
[0005]针对现有技术问题,本发明的目的在于提供一种环保、低廉、可循环的大规模合成ZIF-67材料的方法,以解决现有ZIF-67的合成方法存在产率低,使用大量有机溶剂和能源浪费,操作复杂,条件苛刻、成本高等问题
[0022](1)本发明操作简便,条件简单。在合成过程中,只需将钴盐溶液和二甲基咪唑溶液充分溶解,混合后反应继续搅拌一段时间得到ZIF-67材料。除了真空干燥步骤,其余均是在室温下进行,相对其他技术消耗能源较少,具有节能,低成本和高效的优势。
Smart Images

Figure CN119285970B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of large-scale synthesis of metal-organic frameworks, and specifically relates to an environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 materials. Technical Background
[0002] In the past two decades, metal-organic frameworks (MOFs) have attracted great interest from researchers as emerging porous materials assembled from metal ions / clusters and organic ligands. [Fang Ruiqi. Research on the molecular conversion of biomass furan-based platforms catalyzed by metal-organic framework composite materials [D]. South China University of Technology, 2019.] Compared with traditional porous materials, MOFs have the following advantages: (1) Structural diversity. By adjusting the types of metals and organic ligands, MOFs materials with different structures can be prepared. (2) High specific surface area and porosity. This gives MOFs materials unique advantages in catalysis and gas adsorption. (3) Adjustable material morphology and pore structure. The morphology and pore structure of MOFs materials can be adjusted according to the geometry of organic ligands and their coordination with metal ions / clusters. (4) Contains unsaturated metal sites. During the assembly process, a large number of unsaturated metal sites are usually exposed as catalytic active centers. (5) The preparation process is relatively simple.
[0003] Zeolite imidazolium ester frameworks (ZIFs) are novel metal-organic frameworks (MOFs) composed of transition metal cations (M) and organic imidazolium ester linkers (Im). When the metal (M) component is bridged with a ligand, and the M-Im-M edge is at 145°, a ZIF structure is formed, similar to the Si-O-Si structure in conventional silica-based zeolites. Since 2010, when Yaghi et al. reported the synthesis and structure of ZIFs, numerous studies have focused on their research and applications, such as catalysis, adsorption, and sensing. ZIF-67 is a representative structure, composed of Co... 2+It is coordinated with 2-methylimidazolium and has a sodalite-type framework (SOD) topology. ZIF-67 has excellent microporous structure, high surface area and tunable pore structure, and most of them exhibit excellent thermal stability and chemical stability. Therefore, it has a wide range of applications in gas adsorption, molecular separation, electrochemistry and catalysis. [Zhong G.,Liu D.and Zhang J.The application of ZIF-67 and its derivatives:adsorption, separation, electrochemistry and catalysts[J].Journal of Materials Chemistry A,2018,6(5):1887-1899.] However, these applications are cost-sensitive. If ZIF-67 materials can be synthesized at low cost using energy and raw materials and efficient synthesis methods, it is more likely to improve the utilization value of ZIF-67 materials.
[0004] Currently, methods for synthesizing ZIF-67 materials include hydrothermal, solvothermal, microwave-assisted, sonochemical, and supercritical CO2 methods, with hydrothermal and solvothermal methods being the most common. These methods not only waste a lot of energy but are also environmentally unfriendly, which greatly limits the large-scale synthesis of ZIF-67 materials. For example, hydrothermal and solvothermal methods consume a lot of energy, resulting in resource waste, and the organic solvents used in solvothermal methods are expensive and can also cause potential environmental pollution. For example, the microwave-assisted method (CN110813245A) and the supercritical CO2 method (CN112358623A) can prepare ZIF-67 materials with uniform size, less time consumption, and less environmental pollution, but they have problems such as complex preparation processes, harsh conditions, and high costs. [Qian J., Sun F. and Qin L. Hydrothermal synthesis of zeolitic imidazolate framework-67 (ZIF-67) nanocrystals[J]. Materials Letters, 2012, 82(220-223).] Recently, Qian et al. synthesized imidazolate framework zeolite ZIF-67 nanocrystals in pure water at room temperature. This method is green, energy-efficient, and simple to operate, but it also suffers from low yield and poor morphology. Therefore, from the perspectives of greenness, environmental protection, and economic cost, developing an environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 materials is of great significance. Summary of the Invention
[0005] To address the problems of existing technologies, the present invention aims to provide an environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 materials, thereby solving the problems of low yield, large use of organic solvents and energy waste, complex operation, harsh conditions and high cost of existing ZIF-67 synthesis methods.
[0006] This invention provides an environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 material. The method uses industrial-grade cobalt chloride hexahydrate and industrial-grade 2-methylimidazole as raw materials, n-butylamine as an additive, and tap water as a solvent. The mixture is stirred evenly under room temperature and normal pressure conditions, and then allowed to stand at room temperature for a period of time to obtain a precipitate. After centrifugation, washing, and drying of the precipitate, purple ZIF-67 powder is obtained.
[0007] The objective of this invention is achieved through the following technical solution.
[0008] An environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 materials includes the following steps:
[0009] (1) Add 2-methylimidazole to tap water, stir to dissolve it completely, then add n-butylamine and stir evenly to obtain solution A. Measure the pH of solution A (>10.3), and stop stirring after the value stabilizes.
[0010] (2) Add cobalt chloride hexahydrate to tap water and stir to dissolve it completely to obtain solution B;
[0011] (3) Add solution B to solution A and stir until homogeneous to obtain turbid solution C;
[0012] (4) After the turbid solution C is left to stand at room temperature for a period of time, a precipitate layer is obtained. The precipitate is then separated by centrifugation, washed and other operations to obtain the product. The product is then dried under vacuum to obtain the purple powder ZIF-67 material.
[0013] (5) Take the supernatant above the precipitate layer in step (4), quantify the dimethylimidazole content in the supernatant using GC / MS internal standard method, add a certain amount of dimethylimidazole, stir to dissolve it completely, add a certain amount of n-butylamine and stir evenly to obtain solution A, so that the pH value of solution A is >10.3, and continue to repeat steps (1)(2)(3)(4) at room temperature to obtain purple powder ZIF-67 material.
[0014] Furthermore, the stirring described in steps (1) and (2) is carried out at room temperature, and the cobalt chloride hexahydrate and dimethylimidazole are industrial grade.
[0015] Further, in step (1), the mass concentration of 2-methylimidazole in solution A is 14-15.5 g / L; the molar concentration of n-butylamine is 0.15-0.25 mol / L; and the pH of solution A is stable in the range of 10.6-11.6.
[0016] Furthermore, the mass concentration of cobalt chloride hexahydrate in solution B in step (2) is 35-57 g / L.
[0017] Further, in step (3), the molar ratio of cobalt chloride hexahydrate, dimethylimidazole, n-butylamine, and water in the mixed solution is 1:5:(4.5-6):1851; the stirring speed when mixing solution A and solution B is 200 r / min, and the stirring time is 5 min to 1 h.
[0018] Furthermore, the solution C in step (4) is allowed to stand at room temperature for 24 hours; the washing is done with deionized water; the centrifugation rate is 4000 r / min for 2 minutes; and the drying is done at 100°C under vacuum for 12 hours.
[0019] Further, in step (5), the mass concentration of 2-methylimidazole in the supernatant quantified using the GC / MS internal standard method is 5.5–6.5 g / L; the amount of n-butylamine added is 500 mL. The pH of solution A will be stable in the range of 10.6–10.7.
[0020] Furthermore, the ZIF-67 material prepared using the above steps has a particle size of 4–6 μm and a specific surface area of 1300–1400 m². 2 / g, pore volume 0.55~0.60cm³ 3 / g.
[0021] Compared with the prior art, the present invention has the following advantages or effects:
[0022] (1) This invention is simple to operate and requires minimal conditions. During the synthesis process, it is only necessary to fully dissolve the cobalt salt solution and the dimethylimidazole solution, mix them, and continue stirring the reaction for a period of time to obtain the ZIF-67 material. Except for the vacuum drying step, the rest are carried out at room temperature, which consumes less energy compared to other technologies, and has the advantages of energy saving, low cost and high efficiency.
[0023] (2) The solvent used in this invention is tap water. Traditional methods mostly use organic solvents to prepare ZIF-67 materials, which are toxic, harmful, and difficult to treat, causing certain environmental pollution. Tap water has the advantages of being inexpensive, readily available, and environmentally friendly, making it the best choice of a green and ideal solvent.
[0024] (3) This invention uses industrial-grade cobalt chloride hexahydrate as the cobalt source and industrial-grade 2-methylimidazole as the organic ligand, significantly reducing the cost of raw materials and facilitating large-scale industrial synthesis. Among all cobalt salts, cobalt chloride hexahydrate is relatively inexpensive and causes less environmental pollution. In exploring the influence of cobalt salt type, cobalt chloride hexahydrate is beneficial for forming regular, uniform rhombic dodecahedral ZIF-67 materials. It has been reported that most methods for preparing ZIF-67 materials use a molar ratio of ligand to cobalt salt of 8:1, or even a higher molar ratio. In this invention, a molar ratio of ligand to cobalt salt of 5:1 is used, which is beneficial for forming a more uniform morphology, reduces preparation costs to a certain extent, and avoids waste of organic ligands.
[0025] (4) This invention uses n-butylamine as an additive to deprotonate the intermediate species, significantly improving the yield of the product. Previously, the synthesis of ZIF-67 materials in pure water at room temperature required a large amount of organic ligands, resulting in low yields and potentially leading to a non-porous, dense Dia structure. Using n-butylamine as an additive, the higher alkalinity deprotonates the intermediate species, affecting nucleation and growth rates, thus significantly increasing the yield of ZIF-67 materials (approaching 99%). Furthermore, under suitable alkalinity, the morphology and structure of the ZIF-67 materials are minimally affected. In addition, the waste liquid obtained after large-scale synthesis of ZIF-67 materials can be recycled, reducing the cost of raw material and waste liquid treatment and minimizing pollution.
[0026] (5) This invention proposes an environmentally friendly, inexpensive, and recyclable method for large-scale synthesis of ZIF-67 materials. By adjusting the amount of n-butylamine added in a room-temperature aqueous environment to regulate the alkalinity, not only can the morphology of ZIF-67 materials with large particle size, uniformity, and high crystallinity be obtained, but the yield of synthesized ZIF-67 materials is also greatly improved. By adjusting the formulation parameters at different ratios, the synthesis is scaled up step by step. Large-scale synthesis at high ratios and three cycles of mother liquor recycling were carried out to verify the synthesis of kilogram-scale ZIF-67 materials.
[0027] In summary, this invention offers advantages such as simple operation, low pollution, energy saving, recyclability, and low cost. The synthesis process is carried out at room temperature using tap water as a solvent, which is inexpensive, readily available, and environmentally friendly. The cobalt salt and organic ligands used are all industrial-grade, significantly reducing preparation costs. The waste liquid after the reaction can be recycled, achieving resource utilization by turning waste into treasure. This invention has been validated through large-scale synthesis at high magnification and three cycles of mother liquor recycling, completing experiments to synthesize kilogram-scale ZIF-67 materials. The synthesized ZIF-67 material is relatively uniform and has high crystallinity, making it suitable for large-scale industrial synthesis. Attached Figure Description
[0028] Figure 1 The images show the XRD patterns of the ZIF-67 materials prepared in Examples 1 and 2.
[0029] Figure 2 SEM image of the ZIF-67 material prepared in Example 1;
[0030] Figure 3 This is a SEM image of the ZIF-67 material prepared in the first cycle of Example 2;
[0031] Figure 4 SEM image of ZIF-67 material prepared in the second cycle of Example 2;
[0032] Figure 5 This is a SEM image of the ZIF-67 material prepared in the third cycle of Example 2;
[0033] Figure 6 TGA images of the ZIF-67 materials prepared in Examples 1 and 2;
[0034] Figure 7 The image shows the XRD pattern of the ZIF-67 material prepared in Example 1 after Ar and air heat treatment.
[0035] Figure 8 The image shows the XRD pattern of the ZIF-67 material prepared in Example 1 after boiling water heat treatment.
[0036] Figure 9 The N2 adsorption-desorption isotherm and pore size distribution curve of the ZIF-67 material prepared in Example 1. Detailed Implementation
[0037] The present invention will be further described below with reference to the accompanying drawings and embodiments, but the implementation and protection scope of the present invention are not limited thereto.
[0038] Example 1
[0039] 492.0 g of 2-methylimidazole was weighed and added to 35.0 L of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until completely mixed. Then, 530 mL of n-butylamine was added and the mixture was stirred for another 5 min until completely mixed to obtain solution A. 285.6 g of cobalt chloride hexahydrate was weighed and added to 5.0 L of tap water. The mixture was stirred at 200 r / min for 10 min until completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 1 h to obtain a turbid solution. After standing for 24 h, a distinct precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0040] Example 2
[0041] Take 35.0 L of the supernatant from Example 1, add 292.0 g of 2-methylimidazole, and stir at 200 r / min for 10 min at room temperature until completely mixed. Then add 500 mL of n-butylamine and continue stirring for 5 min until completely mixed to obtain solution A. Weigh 285.6 g of cobalt chloride hexahydrate and add it to 5.0 L of tap water, stirring at 200 r / min for 10 min until completely dissolved to obtain solution B. Pour solution B completely into solution A, stir at 200 r / min for 1 h to obtain a turbid solution, let it stand for 24 h, and a clear precipitate layer appears. Centrifuge and wash the precipitate with deionized water, and vacuum dry at 100 °C for 12 h to obtain the first cycle of purple ZIF-67 powder. Repeat the same operation to obtain the second cycle of purple ZIF-67 powder. Repeat the same operation again to obtain the third cycle of purple ZIF-67 powder.
[0042] The ZIF-67 materials prepared in Examples 1 and 2 were used as representatives for analysis. The analytical results of ZIF-67 materials prepared in other examples are basically the same as those in Example 1, and are not provided one by one.
[0043] (I) Crystal structure and properties of ZIF-67 materials synthesized on a large scale
[0044] The crystal structure of the ZIF-67 materials synthesized on a large scale in Examples 1 and 2 of this invention was characterized using a D8-ADVANCE X-ray diffractometer manufactured by Bruker GmbH, Germany. Figure 1 The PDF standard card for ZIF-67 material and the wide-angle X-ray diffraction patterns of the ZIF-67 material prepared in Examples 1 and 2 of this invention are shown. Figure 1 As can be seen from the data, the ZIF-67 materials prepared in Examples 1 and 2 both showed strong characteristic diffraction peaks of the ZIF-67 metal-organic framework, indicating that the products contain highly crystalline ZIF-67 components.
[0045] (II) Microstructural Properties of Large-Scale Synthesized ZIF-67 Materials
[0046] The microstructure of the ZIF-67 materials prepared in Examples 1 and 2 of this invention was characterized using a Regulus 8100 scanning electron microscope. The results are as follows: Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown, the ZIF-67 materials prepared in Examples 1 and 2 both exhibited large-sized, regular rhombic dodecahedral morphology with relatively uniform size and particle size ranging from 4 μm to 6 μm.
[0047] (III) Stability of ZIF-67 materials synthesized on a large scale
[0048] The thermal stability of the ZIF-67 materials prepared in Examples 1 and 2 of this invention was characterized using a TG209F1 thermogravimetric analyzer. The results are as follows: Figure 6 As shown, the prepared ZIF-67 material exhibits good thermal stability up to 500℃.
[0049] The crystal structure of the ZIF-67 material in Example 1, after heating in Ar atmosphere, air atmosphere, and water, was characterized using a Bruker D8-ADVANCE X-ray diffractometer (Germany). The experimental results are as follows: Figure 7 , 8 As shown, the ZIF-67 material synthesized on a large scale still exhibited strong characteristic diffraction peaks of the ZIF-67 metal-organic framework after calcination at 400°C for 10 hours in an Ar atmosphere, but could only maintain its crystal structure after calcination at 200°C for 10 hours in air; moreover, the ZIF-67 material still exhibited characteristic diffraction peaks of the ZIF-67 metal-organic framework after treatment in boiling water for 5 days; these indicate that the ZIF-67 material prepared in Example 1 of this invention has strong stability.
[0050] (IV) Specific surface area and pore properties of ZIF-67 materials synthesized on a large scale
[0051] The pore properties of the samples prepared in Example 1 of this invention were characterized using an ASAP2460 specific surface area pore size analyzer manufactured by Microtec, USA. The results are shown in Table 1. As can be seen from Table 1, the ZIF-67 material prepared in Example 1 of this invention has a high specific surface area and pore volume.
[0052] Table 1
[0053] ZIF-67 1402.2 0.545
[0054] Figure 9 The N2 adsorption-desorption isotherm of the ZIF-67 material prepared in Example 1 of this invention is derived from... Figure 9 It can be seen that the ZIF-67 material prepared in Example 1 of this invention shows a type I adsorption isotherm. The adsorption amount increases sharply under the pressure of P / P0<0.01. Combined with the results of pore size distribution, it indicates that the sample has a microporous structure.
[0055] Example 3
[0056] 246.0 g of 2-methylimidazole was weighed and added to 17.5 L of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until completely mixed. Then, 270 mL of n-butylamine was added and the mixture was stirred for another 5 min until completely mixed to obtain solution A. 142.8 g of cobalt chloride hexahydrate was weighed and added to 2.5 L of tap water. The mixture was stirred at 200 r / min for 10 min until completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 1 h to obtain a turbid solution. The solution was allowed to stand for 24 h, and a distinct precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0057] Example 4
[0058] 123.0 g of 2-methylimidazole was weighed and added to 8.0 L of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until completely mixed. Then, 130 mL of n-butylamine was added and the mixture was stirred for another 5 min until completely mixed to obtain solution A. 71.4 g of cobalt chloride hexahydrate was weighed and added to 2.0 L of tap water. The mixture was stirred at 200 r / min for 10 min until completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 40 min to obtain a turbid solution. The solution was allowed to stand for 24 h, and a distinct precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0059] Example 5
[0060] 61.5 g of 2-methylimidazole was weighed and added to 4.0 L of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until completely mixed. Then, 65 mL of n-butylamine was added and the mixture was stirred for another 5 min until completely mixed to obtain solution A. 35.7 g of cobalt chloride hexahydrate was weighed and added to 1.0 L of tap water. The mixture was stirred at 200 r / min for 10 min until completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 20 min to obtain a turbid solution. The solution was allowed to stand for 24 h, and a distinct precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0061] Example 6
[0062] 12.3 g of 2-methylimidazole was weighed and added to 800 mL of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until it was completely mixed. Then, 16.5 mL of n-butylamine was added and the mixture was stirred for another 5 min until it was completely mixed to obtain solution A. 7.14 g of cobalt chloride hexahydrate was weighed and added to 200 mL of tap water. The mixture was stirred at 200 r / min for 10 min until it was completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 10 min to obtain a turbid solution. The solution was allowed to stand for 24 h, and a clear precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0063] Example 7
[0064] 12.3 g of 2-methylimidazole was weighed and added to 800 mL of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until it was completely mixed. Then, 16.5 mL of n-butylamine was added and the mixture was stirred for another 5 min until it was completely mixed to obtain solution A. 7.47 g of cobalt acetate tetrahydrate was weighed and added to 200 mL of tap water. The mixture was stirred at 200 r / min for 10 min until it was completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 10 min to obtain a turbid solution. The solution was allowed to stand for 24 h, and a clear precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0065] Example 8
[0066] 12.3 g of 2-methylimidazole was weighed and added to 800 mL of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until it was completely mixed. Then, 13 mL of n-butylamine was added and the mixture was stirred for another 5 min until it was completely mixed to obtain solution A. 8.73 g of cobalt nitrate hexahydrate was weighed and added to 200 mL of tap water. The mixture was stirred at 200 r / min for 10 min until it was completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 10 min to obtain a turbid solution. The solution was allowed to stand for 24 h, and a clear precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0067] Example 9
[0068] 1.23 g of 2-methylimidazole was weighed and added to 80 mL of tap water. The mixture was stirred at 200 r / min for 10 min at room temperature until it was completely mixed. Then, 2.0 mL of n-butylamine was added and the mixture was stirred for another 5 min until it was completely mixed to obtain solution A. 0.714 g of cobalt chloride hexahydrate was weighed and added to 20 mL of tap water. The mixture was stirred at 200 r / min for 10 min until it was completely dissolved to obtain solution B. Solution B was completely poured into solution A and stirred at 200 r / min for 5 min to obtain a turbid solution. The solution was allowed to stand for 24 h and a clear precipitate layer appeared. The precipitate was centrifuged and washed with deionized water and then vacuum dried at 100 °C for 12 h to obtain purple ZIF-67 powder.
[0069] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for large-scale synthesis of ZIF-67 material that is environmentally friendly, inexpensive, and recyclable, characterized in that, It is prepared using industrial-grade cobalt chloride hexahydrate and industrial-grade 2-methylimidazole as raw materials and tap water as solvent, and the waste liquid can be recycled to achieve resource utilization. Specifically, the steps include the following: (1) Add 2-methylimidazole to tap water and stir to dissolve it completely. Then add n-butylamine and stir evenly to obtain solution A. The pH of solution A is measured to be stable in the range of 10.6 to 11.
6. Stop stirring after the value is stable. (2) Add cobalt chloride hexahydrate to tap water and stir to dissolve it completely to obtain solution B; (3) Add solution B to solution A and stir until homogeneous to obtain turbid solution C; the molar ratio of cobalt chloride hexahydrate, dimethylimidazole, n-butylamine and water in the turbid solution C is 1:5:4.5~6:1851; (4) The turbid solution C was allowed to stand at room temperature to obtain a precipitate. The precipitate was then centrifuged and washed to obtain the product. The product was then vacuum dried to obtain the purple powder ZIF-67 material. The turbid solution C was allowed to stand at room temperature for 16-24 hours. The washing was done with deionized water. The centrifugation rate was 4000-5000 r / min for 2-5 minutes. The drying was done at 80-100℃ under vacuum for 12-24 hours. (5) Take the supernatant above the precipitate layer in step (4), quantify the 2-methylimidazole content in the supernatant using GC / MS internal standard method, add 2-methylimidazole to make the mass concentration of 2-methylimidazole in the supernatant 5.5~6.5 g / L, stir to dissolve it completely, then add n-butylamine and stir evenly to obtain solution A, so that the pH value of solution A is stable in the range of 10.6~10.7; continue to repeat steps (1) (2) (3) (4) at room temperature to obtain purple powder ZIF-67 material; In steps (1) and (2), the stirring is carried out at room temperature; in step (1), the mass concentration of 2-methylimidazole in solution A is 14~15.5 g / L; the molar concentration of n-butylamine is 0.15~0.25 mol / L; in step (2), the mass concentration of cobalt chloride hexahydrate in solution B is 35~57 g / L; in step (3), the stirring speed when mixing solution A and solution B is 200~300 r / min, and the stirring time is 5 min~1 h; in step (4), the washing is carried out with deionized water; the centrifugation rate is 4000~5000 r / min, and the time is 2~5 min; the drying is vacuum drying at 80~100℃, and the drying time is 12~24 h; in step (5), the amount of n-butylamine added is 500 mL; The ZIF-67 material prepared by the method has a particle size of 4~6μm, a specific surface area of 1300~1400 m² / g, and a pore volume of 0.55~0.60 cm³ / g.
2. The ZIF-67 material prepared by the method of claim 1 has a particle size of 4~6μm, a specific surface area of 1300~1400 m² / g, and a pore volume of 0.55~0.60 cm³ / g.
Citation Information
Patent Citations
Method for preparing ZIF-67 adsorbent by steam-assisted method and application of ZIF-67 adsorbent in cyclohexane adsorption
CN110813245A
Method for synthesizing zeolitic imidazolate framework metal organic material ZIF-67 in supercritical CO2
CN112358623A
Method for preparing zeolite imidazate framework material
CN105985362A
Green and economic large-scale synthesis method of ZIF-8 material
CN116041717A
Method for large-scale synthesis of Zn / Co-ZIF material at room temperature and normal pressure
CN118240232A